2019
DOI: 10.3892/ol.2019.10541
|View full text |Cite
|
Sign up to set email alerts
|

Multi‑kinase inhibitors and cisplatin for head and neck cancer treatment in vitro

Abstract: Multidrug resistance (MDR) remains one of the major causes of suboptimal outcome following therapy in head and neck squamous cell carcinoma (HNSCC). ATP-binding cassette (ABC) transporters are overexpressed in HNSCC, which contributes to the limited effect of chemotherapeutic treatment. In addition to their named function, tyrosine kinase inhibitors (TKIs) have been revealed to impact on ABC transporter activity and expression. Therefore, the present study aimed to investigate the effects of combination therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…In a previous study, [30] has demonstrated that dihydroartemisinin (derivative of artemisinin) caused an apoptosis in nonsmall cell lung cancer cells with EGFR or RAS mutation in-vitro and in-vivo. [31] found that after cisplatin treatment intermediate and low levels of FGFR3 and FGFR4 were expressed in all ve head and neck squamous cell carcinoma cell lines. Where, tumor growth or neoangiogenesis, as angiogenesis serves is a critical role in tumor growth, and the inhibition of this process via cisplatin alone is insu cient.…”
Section: Discussionmentioning
confidence: 94%
“…In a previous study, [30] has demonstrated that dihydroartemisinin (derivative of artemisinin) caused an apoptosis in nonsmall cell lung cancer cells with EGFR or RAS mutation in-vitro and in-vivo. [31] found that after cisplatin treatment intermediate and low levels of FGFR3 and FGFR4 were expressed in all ve head and neck squamous cell carcinoma cell lines. Where, tumor growth or neoangiogenesis, as angiogenesis serves is a critical role in tumor growth, and the inhibition of this process via cisplatin alone is insu cient.…”
Section: Discussionmentioning
confidence: 94%
“…Preclinically, an in vitro study investigated the combination of various MKIs with cisplatin in SCCHN cell lines. Nintendanib was noted to exert the greatest synergistic effect with cisplatin chemotherapy ( 70 ). Phase I trials in patients with head and neck cancer showed adequate tolerance ( 71 , 72 ).…”
Section: Vegf-tkis In Scchnmentioning
confidence: 99%
“…In preclinical models of OSCC, combination therapy of cisplatin and inhibitors of VEGFR (i.e., pazopanib and nintedanib) was more potent than treatment with chemotherapy alone ( 38 ). The efficacy and toxicity of docetaxel with or without vandetanib, an inhibitor of VEGFR, RET, and EGFR, was investigated in patients with advanced recurrent or metastatic HNSCC.…”
Section: Mechanisms Of Resistance To Chemotherapymentioning
confidence: 99%